Data processing method for magnetotelluric sounding based on cepstral analysis - Zhan, Qining; Liu, Cai; Liu, Yang; Zhao, Pengfei (Frontiers in Earth Science, 2023)
a wide frequency band. The acquired field data is susceptible to various types of noise, which poses challenges in accurate identification and processing. Currently, there are numerous MT data processing methods available; however, they lack efficiency and physical meaning. To address this issue and improve the signal-to-noise ratio of the acquired data, this study proposes a method of MT data processing based on cepstral analysis. By employing cepstral analysis on the MT data, the cepstrum is obtained, and an appropriate truncation position is selected for processing. The experimental results demonstrate that this method obtains smoother and more continuous apparent resistivity curves with less errors. Compared with other methods, the cepstral analysis method can effectively suppress different types of MT noise, and the method is simple and efficient with clear physical significance.